Diferença cultural, políticas e representações sobre inclusão escolar de imigrantes bolivianos no Município de São Paulo - Masella, Ana Paula Ignacio (2019)
This research focuses on the reality of immigration, present worldwide and locally, which is expressed in a problem that involves this phenomenon in various dimensions, highlighting issues of a socio-cultural and educational nature. The guiding objective of the study is to focus on the school inclusion of Bolivian immigrants in the public school system of the city of São Paulo, within the scope of public policies and student representations in this context. The methodology is characterized by the qualitative approach that bases the bibliographic research and the documentary analysis as adopted procedures. The most expressive results of the analyzes carried out indicate a significant number of Bolivian immigrants living in the city of São Paulo and the need to promote a plural and inclusive education that ensures the access and permanence of these students in educational units on equal terms, preserving their origin culture. The public policies associated with this scenario indicate that migratory flows, interculturality and the emancipating curriculum are relevant parameters for the structuring of a school for all, and require teacher training consistent with the emerging demands of this context